The disappointment centre of the brain gets exciting: a systematic review of habenula dysfunction in depression - Sarah Cameron; Katrina Weston-Green; Kelly A. Newell (Translational Psychiatry)
Abstract Background The habenula is an epithalamic brain structure that acts as a neuroanatomical hub connecting the limbic forebrain to the major monoamine centres. Abnormal habenula activity is increasingly implicated in depression, with a surge in publications on this topic in the last 5 years. Direct activation of the habenula is sufficient to induce a depressive phenotype in rodents, suggesting a causative role in depression. However, the molecular basis of habenula dysfunction in depression remains elusive and it is unclear how the preclinical advancements translate to the clinical field. Methods A systematic literature search was conducted following the PRISMA guidelines. The two search terms depress* and habenula* were applied across Scopus, Web of Science and PubMed databases. Studies eligible for inclusion must have examined the habenula in clinical cases of depression or preclinical models of depression and compared their measures to an appropriate control. Results Preclinical studies (n = 63) measured markers of habenula activity (n = 16) and neuronal firing (n = 22), largely implicating habenula hyperactivity in depression. Neurotransmission was briefly explored (n = 15), suggesting imbalances within excitatory and inhibitory habenula signalling. Additional preclinical studies reported neuroconnectivity (n = 1), inflammatory (n = 3), genomic (n = 3) and circadian rhythm (n = 3) abnormalities. Seven preclinical studies (11%) included both males and females. From these, 5 studies (71%) reported a significant difference between the sexes in at least one habenula measure taken. Clinical studies (n = 24) reported abnormalities in habenula connectivity (n = 15), volume (n = 6) and molecular markers (n = 3). Clinical studies generally included male and female subjects (n = 16), however, few of these studies examined sex as a biological variable (n = 6). Conclusions Both preclinical and clinical evidence suggest the habenula is disrupted in depression. However, there are opportunities for sex-specific analyses across both areas. Preclinical evidence consistently suggests habenula hyperactivity as a primary driver for the development of depressive symptoms. Clinical studies support gross habenula abnormalities such as altered activation, connectivity, and volume, with emerging evidence of blood brain barrier dysfunction, however, progress is limited by a lack of detailed molecular analyses and limited imaging resolution.